IMPLEMENTASI PERAN PEMERINTAHAN DAERAH DALAM PELESTARIAN POPULASI IKAN BILIH DI DANAU SINGKARAK BERDASARKAN PERATURAN GUBERNUR NOMOR 81 TAHUN 2017 - Intan Elmayu Putri; Syamsir Syamsir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research explains the role of regional governance in the preservation of the Bilih fish population in Lake Singkarak based on Gubenur regulation No 81 year 2017. Research aims to describe the role of local governance, constraints and efforts of local governance. Methods used are qualitative methods. Data is derived from documentation studies, interviews, and observations. Things that are considered in collecting data in the selection of informant among them to the community, community leaders, head of the field of capture and head of PRL and PSDKP and Walinagari. Based on the results of the research conducted in the service can be concluded: first, the role of the Marine Service and fisheries of West Sumatra province in the preservation of Bilih fish populations in the use of Centrum, Putas/poison, the vacuum and mesh that the net eyes are too tightly in Lake Singkarak. Second, the Marine Service and fisheries of West Sumatra province which is seen from external and internal constraints which is a constraint for the government in the preservation of Bilih fish populations in the use of Centrum, Putas/poison, and nets and mesh that the net eyes are too tightly in Lake Singkarak. Third, the efforts undertaken by the local government in stopping the constraints that occur: 1) DKP that conducts coaching to the fishermen community in providing training, awareness, counseling, and socialization of the preservation of the population of Bilih fish in Lake Singkarak; 2) The Government has the purpose of providing the assistance of an environmentally friendly arrest tool to the fishermen who operate the fishing equipment in the lake Salingka; 3) Conduct raids to the fishermen communities that operate the use of Centrum, Putas/poison, the vacuum and nets that the net eye is too tightly in Lake Singkarak; 4) The plan to propose the government budget to the preservation of Bilih fish in Lake Singkarak has not been running in accordance with the role of the Government on the construction and supervision of this still many fishermen people who use the Centrum, Putas/poison, the vacuum and nets that the net is too tightly in Lake Singkarak.